2023
DOI: 10.1177/15248380231153864
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Lifestyle-Routine Activity Theory in the Context of Direct-Contact Sexual Victimization

Abstract: Studies have extended and applied lifestyle-routine activity theory (L-RAT) to direct-contact sexual violence (SV). Yet, operationalizations of theoretical concepts—exposure, proximity, target suitability, and guardianship—have not been consistent across studies within this context, and therefore the ultimate conclusions on the robustness of the theory remain an open empirical question. In this systematic review, we compile scholarship on the application of L-RAT to direct-contact SV to identify how core conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
(311 reference statements)
0
2
0
Order By: Relevance
“…Independent variables are informed by prior research on the association between routine activities and IPV (Hayes, 2018(Hayes, , 2022 and forms of sexual violence (Fisher et al, 2010;Franklin et al, 2012;Hayes et al, 2021;Hayes & Maher, 2023;Mustaine & Tewksbury, 2002;Schwartz et al, 2001;Schwartz & Pitts, 1995).…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent variables are informed by prior research on the association between routine activities and IPV (Hayes, 2018(Hayes, , 2022 and forms of sexual violence (Fisher et al, 2010;Franklin et al, 2012;Hayes et al, 2021;Hayes & Maher, 2023;Mustaine & Tewksbury, 2002;Schwartz et al, 2001;Schwartz & Pitts, 1995).…”
Section: Independent Variablesmentioning
confidence: 99%
“…Others have also found that behaviorally bisexual women are at an increased risk of reproductive coercion (Alexander et al, 2016). Indeed, when this item has been considered in prior scholarship on the application of routine activity theory to sexual violence, it has been a robust measure (Hayes et al, 2021; Hayes & Maher, 2023; Snyder, 2015; Sutton et al, 2021). As suggested by Sween and Reyns (2017), sexual orientation may be related to the target congruence framework in terms of offender perceptions of target antagonism (i.e., behaviors or identities that enhance anger, hostility, jealousy, or resentment within the offender) or target gratification (i.e., the potential victim has characteristics that the offender wants to use, have access to, or manipulate), thereby enhancing perceptions of target suitability (Finkelhor & Asdigian, 1996).…”
Section: Reproductive Coercionmentioning
confidence: 99%